Prevalensi HBsAg Positif Antara Donor Darah Sukarela Dengan Donor Darah Pengganti Di UTD PMI Provinsi Lampung Tahun 2019-2020 - Sari Rahmada Mulyani; Aditya Aditya; Festy Ladyani Mustofa; Zulfian Zulfian (Universitas Malahayati, 2021)
ABSTRACT: PREVALENCE OF POSITIVE HBsAg BETWEEN VOLUNTARY BLOOD DONATIONS AND REPLACEMENT BLOOD DONATIONS AT PMI UTD LAMPUNG PROVINCE 2019-2020 Background: The risk of transmission of HBV infection through blood transfusion depends on many things, including the prevalence of disease in the community, the recipient's immune status, the number of donors per unit of blood, and the effectiveness of the screening used. The main disease transmission will occur during the window period, which is a period immediately after infection in which the donor's blood has been infected but the screening result is still negative.Objective: To determine the prevalence of positive HBsAg between voluntary blood donations and replacement blood donations at the PMI UTD in Lampung Province in 2019-2020. Methodology: The type of research used in this research is quantitative descriptive with cross-sectional design. The sample used in this study were blood donors at UTD PMI Lampung Province in 2019-2020.Results: The prevalence of voluntary blood donation with positive HBsAg in 2019 was obtained as many as 70 people (33.65%) while the prevalence of replacement blood donors with positive HBsAg in 2019 was obtained as many as 8 people (16%). Then, the prevalence of positive HBsAg voluntary blood donors in 2020 was found to be 138 people (66.35%) while the prevalence of positive HBsAg blood donors in 2020 was 42 people (84%).Conclusion: There is a difference in the prevalence of both voluntary blood donors and replacement blood donors between 2019 and 2020. and the prevalence of HBsAg positive in blood donors is different every year. Keywords: Blood Transfusion, Volunteer, Replacement, HBsAg INTISARI: PREVALENSI HBsAg POSITIF ANTARA DONOR DARAH SUKARELA DENGAN DONOR DARAH PENGGANTI DI UTD PMI PROVINSI LAMPUNG TAHUN 2019-2020 Latar Belakang: Risiko penularan pada infeksi HBV melalui transfusi darah bergantung pada banyak hal, antara lain yaitu adanya prevalensi penyakit pada masyarakat, status imun resipien, jumlah donor tiap unit darah dan keefektifan skrining yang di gunakan. Penularan penyakit yang utama akan timbul pada saat window period, yaitu suatu periode segera terjadi setelah terinfeksi dimana darah donor sudah terinfeksi tetapi hasil skrining masih negative.Tujuan: Mengetahui Prevalensi HBsAg Positif Antara Donor Darah Sukarela Dengan Donor Darah Pengganti Di UTD PMI Provinsi Lampung Tahun 2019-2020.Metodologi: Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dengan desain cross sectional. Sampel yang digunakan pada penelitian ini adalah pendonor darah di UTD PMI Provinsi Lampung tahun 2019-2020.Hasil: Prevalensi donor darah sukarela dengan HBsAg positif pada tahun 2019 didapatkan sebanyak 70 orang (33,65%) sementara prelavensi donor darah pengganti dengan HBsAg positif pada tahun 2019 didapatkan sebanyak 8 orang (16%). Lalu, prevalensi donor darah sukarela dengan HBsAg positif pada tahun 2020 didapatkan sebanyak 138 orang (66,35%) sementara untuk prevalensi donor darah pengganti dengan HBsAg positif pada tahun 2020 didapatkan sebanyak 42 orang (84%).Kesimpulan: Terdapat perbedaan prevalensi baik donor darah sukarela maupun donor darah pengganti antara tahun 2019 dengan tahun 2020. Dan prevalensi HBsAg Positif pada donor darah berbeda-beda setiap tahun. Kata Kunci : Donor Darah, Sukarela, Pengganti, HBsAg